MOST RECENT FALL DEPOSITS OF KSUDACH VOLCANO, KAMCHATKA, RUSSIA - Bursik M.; Melekestsev I.V.; Braitseva O.A. (My University, 1993)
Three of four Plinian eruptions from Ksudach Volcano are among the four largest explosive eruptions in southern Kamchatka during the past 2000 years. The earliest of the eruptions was voluminous and was accompanied by an ignimbrite and the fifth and most recent caldera collapse event at Ksudach. The isopach pattern is consistent with a column height of 23 km. The three more recent and smaller eruptions were from the Shtyubel' Cone, within the fifth caldera. Using isopach and grain size isopleth patterns, column heights ranged from ≥ 10 to 22 km. Although the oldest eruption may have produced a large acidity peak in the Greenland ice, the three Shtyubel' events may not be related to major acid deposition. Thus it is possible that few if any of the uncorrelated acidity peaks of the past 2000 years in Greenland ice cores result from eruptions in southern Kamchatka.
Keywords: 38.37.25 Вулканология; Ксудач